1994
DOI: 10.1530/eje.0.1310598
|View full text |Cite
|
Sign up to set email alerts
|

Oral dexamethasone administration: new pharmacological test for the assessment of growth hormone secretion

Abstract: Acute intravenous (i.v.) dexamethasone administration has been described recently as a new test for the diagnosis of growth hormone (GH) deficiency. In the present study, a new protocol of dexamethasone administration was evaluated. Twelve normal adults and 18 normal prepubertal children were studied. The dexamethasone i.v. test was performed in six adults at a dose of 4 mg and 12 children at a dose of 2 mg/m2. Blood samples were collected 15 min before, at time zero and every 15 or 30 min during 5 h, resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
(14 reference statements)
1
6
0
Order By: Relevance
“…The positive e ect of the exogenous corticosterone on the secretion of GH reported here accords with data from a number of clinical studies which have demonstrated prompt increases in serum GH following acute administration of glucocorticoids by mouth or parenterally (Buguera et al, 1990;Casanueva et al, 1990;Muruais et al, 1991;Pineda et al, 1994;Pinto et al, 1997;Pellini et al, 1998) and advocated a role for GCs in the diagnosis of GH de®ciency (Pineda et al, 1994;Pellini et al, 1998). Our ®nding that the hypersecretion of GH provoked by a single injection of corticosterone in the rat is (a) blocked speci®cally by central but not peripheral administration of anti-annexin 1 pAb and (b) mimicked by a central injection of annexin 1 Ac2 ± 26 suggests that the steroid exerts its positive in¯uence on the GH axis via an annexin 1-dependent mechanism within the hypothalamus.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The positive e ect of the exogenous corticosterone on the secretion of GH reported here accords with data from a number of clinical studies which have demonstrated prompt increases in serum GH following acute administration of glucocorticoids by mouth or parenterally (Buguera et al, 1990;Casanueva et al, 1990;Muruais et al, 1991;Pineda et al, 1994;Pinto et al, 1997;Pellini et al, 1998) and advocated a role for GCs in the diagnosis of GH de®ciency (Pineda et al, 1994;Pellini et al, 1998). Our ®nding that the hypersecretion of GH provoked by a single injection of corticosterone in the rat is (a) blocked speci®cally by central but not peripheral administration of anti-annexin 1 pAb and (b) mimicked by a central injection of annexin 1 Ac2 ± 26 suggests that the steroid exerts its positive in¯uence on the GH axis via an annexin 1-dependent mechanism within the hypothalamus.…”
Section: Discussionsupporting
confidence: 88%
“…This is due largely to actions of the steroids at the hypothalamic level which increase the expression and release of somatostatin (Papachristou et al, 1994;Fife et al, 1996;Lam & Srivastava, 1997) and decrease the production of GH releasing hormone (GHRH, Fernandez-Vazquez et al, 1995;Fife et al, 1996;Lam & Srivastava, 1997). Paradoxically, the impact of the consequent change in the hypothalamic drive to the somatotrophs is attenuated by concomitant actions of the steroids at the pituitary level which increase GHRH receptor (Tamaki et al, 1996;Miller & Mayo, 1997) and GH (Oosterom et al, 1983;Evans et al, 1992;Nogami et al,complicated by ®ndings in man that acute administration of GCs causes a transient (3 ± 4 h), but marked, increase in serum GH (Buguera et al, 1990;Casanueva et al, 1990;Muruais et al, 1991;Pineda et al, 1994;Pinto et al, 1997;Pellini et al, 1998). The mechanism by which the GCs evoke this secretory response is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Maxi mal values were observed after 120 and 150 min in the majority of the subjects. In adults, maximal GH eleva tions occur between 120 and 240 min, with predomi nance at 180 min [20], Pineda et al [25] have demon strated that children are more responsive to dexametha sone in terms of peak values, although no differences were observed in the AUC. This could suggest that children tend to have an earlier onset and a shorter duration of action associated with a higher amplitude of response.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is apparently independent of the type of steroid used [22]. Moreover, in adults, different doses of dexamethasone (8, 4 and 2 mg) have been employed with equal effectiveness [20,23,24], The GH-stimulatory effect is observed when corticoids are used by both intravenous or oral routes of administration [20,25], In obesity and acromegaly the GH-releasing action of intravenous dexamethasone ad ministration has not been verified [21,22,26,27],…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation